Immersive virtual environment as a learning tool for data structures and algorithms - Soussa, Márcio; de Brito, Gabriel; Vianna, Tiago; Araújo, Pedro Henrique; Alberto, Carlos; Ferreira, Yasmim Thasla Santos; Santos, Sanval; Lima, Claudia; Winkler, Ingrid (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
The abstract nature of data structures and algorithms remains a challenge in computer science education. This study aims to design and develop an educational tool based on metaverse and virtual reality technologies to support the teaching and learning of data structures and algorithms. A Design Science Research methodology was adopted, involving the development of an immersive learning tool available in two formats: a virtual reality version and a metaverse version. To evaluate the tool, questionnaires were administered at two distinct moments. Initially, a group of forty students assessed the tool, focusing on the didactic effectiveness of the experience alongside a usability survey. Subsequently, a second group of eight students was surveyed to examine both usability and immersion aspects of the tool. As a result, the tool demonstrated significant gains in conceptual understanding for undergraduate students (p < 0.05), particularly with respect to stacks and queues. Usability assessments, using the System Usability Scale, yielded positive scores (80 and 75.3), suggesting ease of use. However, the Igroup Presence Questionnaire score of 2.92 indicated a lower sense of immersion, which could impact user engagement. These findings suggest that, while the tool effectively enhances conceptual understanding, interactive elements need refinement to optimize immersion and practical problem-solving transfer. The study provides an evaluated immersive tool and empirical evidence with potential implications for virtual learning environments. Future work should focus on addressing immersion gaps and improving practical application transfer to further consolidate the proposed contribution.